Influencing Factors of Student Migration for Abroad Study - Adhikari, Shukra Raj (SMC Journal of Sociology, 2025)
Migration refers to the process of a group of individuals moving from one location to another. One specific type of migration is student migration for studying abroad, which falls under the category of international migration. This research focuses on exploring the factors that influence student migration for education abroad. Twenty cases were selected using purposive and snowball sampling methods from a group of students interested in studying abroad. A content analysis method was employed to analyze both primary and secondary data. In Nepal, student migration has been rapidly increasing over the past decade, as many seek sustainable career opportunities. The country struggles to retain its youth due to a lack of well-paying job opportunities that offer respect and stability, compounded by political uncertainty, which leads to widespread frustration. Many students feel uncertain about their prospects if they remain in Nepal, prompting a sense of hopelessness that drives them to consider studying abroad—often seen as a more viable option. They are particularly attracted to developed nations. The data aligns with the assumptions of the theory of the mode of production and the theory of globalization.